Боевой расчет: [роман] / Александр Тамоников - Тамоников Александр Александрович (Спецназ, 2013)
Экземпляры: ф.11 (20151130) / Инвентарный номер: 059957 / Цена: 100.00 / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6